Developmental pruning of sensory neurites by mechanical tearing in Drosophila. - Krämer, R.; Wolterhoff, N.; Galic, M.; Rumpf, S. (Journal of Cell Biology, 2023)
Mechanical forces actively shape cells during development, but little is known about their roles during neuronal morphogenesis. Developmental neurite pruning, a critical circuit specification mechanism, often involves neurite abscission at predetermined sites by unknown mechanisms. Pruning of Drosophila sensory neuron dendrites during metamorphosis is triggered by the hormone ecdysone, which induces local disassembly of the dendritic cytoskeleton. Subsequently, dendrites are severed at positions close to the soma by an unknown mechanism. We found that ecdysone signaling causes the dendrites to become mechanically fragile. Severing occurs during periods of increased pupal morphogenetic tissue movements, which exert mechanical forces on the destabilized dendrites. Tissue movements and dendrite severing peak during pupal ecdysis, a period of strong abdominal contractions, and abolishing ecdysis causes non-cell autonomous dendrite pruning defects. Thus, our data establish mechanical tearing as a novel mechanism during neurite pruning.